2016
DOI: 10.1007/s00299-016-2045-4
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid ω-hydroxylases from Solanum tuberosum

Abstract: Potato StCYP86A33 complements the Arabidopsis AtCYP86A1 mutant, horst - 1. Suberin is a cell-wall polymer that comprises both phenolic and aliphatic components found in specialized plant cells. Aliphatic suberin is characterized by bi-functional fatty acids, typically ω-hydroxy fatty acids and α,ω-dioic acids, which are linked via glycerol to form a three-dimensional polymer network. In potato (Solanum tuberosum L.), over 65 % of aliphatics are either ω-hydroxy fatty acids or α,ω-dioic acids. Since the biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…The sequencing of the potato genome (Xu et al ., ) has opened the door to discovery of putative regulatory elements of known suberin biosynthesis genes, providing clues to potential mechanisms that govern their expression. For example, we recently demonstrated that the 1.7‐kb region upstream of the StCYP86A33 open reading frame contains over 40 ABA‐response or ABA‐response‐like motifs, supporting a role for ABA in the regulation of this important aliphatic suberin biosynthesis gene (Bjelica et al ., ). While the general involvement of ABA in suberin deposition in potato tubers in response to wounding has already been demonstrated (Soliday et al ., ; Cottle and Kolattukudy, ; Lulai et al ., ; Kumar et al ., ), whether both phenolic and aliphatic metabolisms are affected by this plant hormone remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The sequencing of the potato genome (Xu et al ., ) has opened the door to discovery of putative regulatory elements of known suberin biosynthesis genes, providing clues to potential mechanisms that govern their expression. For example, we recently demonstrated that the 1.7‐kb region upstream of the StCYP86A33 open reading frame contains over 40 ABA‐response or ABA‐response‐like motifs, supporting a role for ABA in the regulation of this important aliphatic suberin biosynthesis gene (Bjelica et al ., ). While the general involvement of ABA in suberin deposition in potato tubers in response to wounding has already been demonstrated (Soliday et al ., ; Cottle and Kolattukudy, ; Lulai et al ., ; Kumar et al ., ), whether both phenolic and aliphatic metabolisms are affected by this plant hormone remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…SFs that can hydrolyze sulfate esters have crucial roles in a broad range of organisms. They are classified into three mechanistically and structurally distinct groups: the alkylsulfatases from the α‐ketoglutarate‐dependent dioxygenase family, the Zn‐dependent alkylsulfatases, and the formylglycine‐dependent sulfatases (Diez‐Roux and Ballabio, ; Toesch et al ., ; Bjelica et al ., ). In the E .…”
Section: Resultsmentioning
confidence: 97%
“…SFs that can hydrolyze sulfate esters have crucial roles in a broad range of organisms. They are classified into three mechanistically and structurally distinct groups: the alkylsulfatases from the a-ketoglutaratedependent dioxygenase family, the Zn-dependent alkylsulfatases, and the formylglycine-dependent sulfatases (Diez-Roux and Ballabio, 2005;Toesch et al, 2014;Bjelica et al, 2016). In the E. histolytica genome, five putative SFs are encoded (Supporting Information Figs S4 and S5A, Table S1), and their amino acid sequences show significant identity with those of the Zn-dependent alkylsulfatases (32.0-40.1%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations